Analyse démogénétique de la contribution des fondateurs irlandais au peuplement du Québec et de ses régions - Letendre, Maude (Université Laval et Université du Québec à Chicoutimi, 2007)
Keywords: Irlandais

Les Irlandais à Montréal. Une présence marquante dès le XIXe siècle - Jolivet, Simon (Montréal en tête, 2013)
Keywords: Irlandais; Saint-Patrick (paroisse)

Les Irlandais catholiques de Montréal : genèse d'une communauté, 1800-1834 - Duchesne, Jonathan (Université du Québec à Montréal, 2021)
Keywords: Famille; Irlandais; Mariage

Les Irlandais et le canal de Lachine. La grève de 1843 - Boily, Raymond (Leméac, 2011)
Keywords: Grèves; Irlandais; Lachine (canal)

L'hostilité entre Irlandais catholiques et Irlandais protestants. La Saint-Barthélemy de Montréal (1853) - Germain, Jean-Claude (Montréal en tête, 2013)
Keywords: Gavazzi, Alessandro; Irlandais; Protestants; Émeutes

Britannique et Irlandaise: l'identité ethnique et démographique des Irlandais protestants et la formation d'une communauté à Montréal, 1834-1860 - Timbers, Wayne (Université McGill, 2001)
Keywords: Britanniques; Irlandais; Protestants

Saint-Patrick et les paroissiens irlandais - Olson, Sherry (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Irlandais; Saint-Patrick (église); Sulpiciens; Églises

Trois leaders irlandais au Bas-Canada - Rompré, Mathieu (Cap-aux-Diamants, 2007)
Keywords: Irlandais; O'Callaghan, Edmund B.; Tracey, Daniel; Waller, Jocelyn

The Challenge of the Irish Catholic Community in Nineteenth-Century Montreal - Olson, Sherry; Thornton, Patricia (Histoire sociale / Social History, 2002)
Keywords: Irlandais

“If the evil now growing around us be not staid”: Montreal and Liverpool Confront the Irish Famine Migration as a Transnational Crisis in Urban Governance - Horner, Dan (Histoire sociale / Social History, 2013)
Keywords: Irlandais

Orange, vert et bleu: les orangistes au Québec depuis 1849 - Jolivet, Simon (Bulletin d'histoire politique, 2010)
Keywords: Irlandais

Irish-Catholic Leadership in Nineteenth Century Montreal - Leitch, Gillian (Cahiers d'histoire, 2003)
Keywords: Irlandais

Port Cities in Crisis: Considering Urban Governance, Modernity and Migration in Mid-Nineteenth-Century Montreal and Liverpool in a Transnational Context - Horner, Dan (Cities Beyond Borders: Comparative and Transnational Approaches to Urban History, 2015)
Keywords: Irlandais

A Population Takes Flight: The Irish Famine Migration in Boston, Montreal, and Liverpool, and the Politics of Marginalization and Criminalization - Horner, Dan (The Criminalization of Migration: Context and Consequences, 2018)
Keywords: Irlandais

The harp and the shamrock: the two faces of Montreal's Irish community - Bâby, Françoise (The Westmount Historian, 2023)
Keywords: Griffintown; Irlandais

Irish Politics on Parade: The Clergy, National Societies, and St. Patrick's Day Processions in Nineteenth-century Montreal and Toronto - Trigger, Rosalyn (Histoire sociale / Social History, 2004)
Keywords: Irlandais; Processions

Silver and Hotcakes and Beer: Irish Montreal in the 1840s - Olson, Sherry (Canadian Ethnic Studies / Études ethniques au Canada, 2013)
Keywords: Auberges; Irlandais

An Irish heart: how a small immigrant community shaped Canada - Doyle Driedger, Sharon (HarperCollins Publishers, 2011)
Keywords: Griffintown; Irlandais; Quartiers

Solemn Processions and Terrifying Violence: Spectacle, Authority, and Citizenship during the Lachine Canal Strike of 1843 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2010)
Keywords: Grèves; Irlandais; Lachine (canal)

The Radicalization of the Montreal Irish: The Role of the "Vindicator" - Jackson, James (The Canadian Journal of Irish Studies, 2005)
Keywords: Irlandais; Rébellions; The Vindicator

Trouble at the Edge of Town: Policing Montreal’s Urban Periphery in the Middle of the Nineteenth Century - Horner, Dan (Micro-Geographies of the Western City, c.1750-1900, 2020)
Keywords: Irlandais; Lachine (canal); Police

Anglicans and the Atlantic World: High Churchmen, Evangelicals and the Quebec Connection - Vaudry, Richard W. (McGill-Queen's University Press, 2003)
Keywords: Anglicans; Britanniques; Irlandais; Protestants

L'émeute Gavazzi: violence et liberté d'expression au milieu du XIXe siècle - Breton, Vincent (Bulletin d'histoire politique, 2006)
Keywords: Gavazzi, Alessandro; Irlandais; Protestants; Émeutes

The Riot that Never Was: The Military Shooting of Three Montrealers in 1832 and the Official Cover-Up - Jackson, James (Baraka Books, 2009)
Keywords: Armée; Irlandais; Tracey, Daniel; Émeutes

L’émeute Gavazzi: pouvoir et conflit religieux au Québec au milieu du 19e siècle - Breton, Vincent (Université du Québec à Montréal, 2004)
Keywords: Gavazzi, Alessandro; Irlandais; Protestants; Émeutes

L'émeute inventée - Jackson, James (VLB, 2014)
Keywords: Armée; Irlandais; Tracey, Daniel; Émeutes

Prosélytisme et conflits religieux lors de l’épidémie de typhus à Montréal en 1847 - Charest, Maude (Cap-aux-Diamants, 2013)
Keywords: Communautés religieuses; Irlandais; Protestants; Épidémies

A Rooted Horror: Thomas D'Arcy McGee and Secret Societies, 1845-68 - A. Wilson, David (The Canadian Journal of Irish Studies, 2005)
Keywords: Féniens; Irlandais; McGee, Thomas D'Arcy; Nationalisme

Ethnic Partition of the Work Force in 1840s Montréal - Olson, Sherry (Labour / Le travail, 2004)
Keywords: Anglophones; Britanniques; Français; Irlandais; Protestants; Travail

St. Patrick's and the Irish Catholics - Olson, Sherry (The Sulpicians of Montreal: a history of power and discretion, 1657-2007, 2013)
Keywords: Communautés religieuses; Irlandais; Saint-Patrick (église); Sulpiciens; Églises

Shame upon you as men!: Competing Visions of Masculine Authority in the Aftermath of Montreal's Gavazzi Riot - Horner, Dan (Gender History: Canadian Perspectives, 2014)
Keywords: Britanniques; Canadiens français; Gavazzi, Alessandro; Irlandais; Émeutes

Population, identités sociales et vie quotidienne - Gauvreau, Danielle (Histoire de Montréal et de sa région, 2012)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Population, Social Identities, and Daily Life - Gauvreau, Danielle (Montreal: The History of A North American City, 2018)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Témoins discrets - Leclerc, Jean-François (Continuité, 2019)
Keywords: Chinois; Grecs; Irlandais; Italiens; Juifs; Noirs; Patrimoine; Syriens

Louis-Joseph Papineau et le Bas-Canada pré-1837 - Guyot, Julie (Les Insoumis de l'Empire. Le refus de la domination coloniale au Bas-Canada et en Irlande, 2016)
Keywords: Papineau, Louis-Joseph

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail